Building the capacity of learning professionals through an infusion of formal and informal learning - Bolt, Susan (Common Ground, 2008)
The success of many organisations depends on their capacity to learn and because of this learning professionals in the fields of education and training are often engaged to build workforce capacity. The success of this scenario depends on the expertise of these learning professionals, but how is their capacity built? Formal learning is typically standardised, centrally controlled and vertically integrated approaches to the transmission of knowledge through organised curriculum modules that can lead to a qualification. Informal learning is more horizontally integrated, dynamic and occurs when peoplemake a conscious effort to learn from their experiences and engage in individual or group reflection (Burns, 2002; Foley, 2004). In the past formal and informal learning were considered separately but an infusion of formal and informal learning may be a more appropriate approach in this new economy. This paper, based on results from an interpretive study investigating professional development in large Australian organisations in 2007, explores the professional development experiences of staff employed in training and educational organisations. Semi-structured interviews and questionnaires, using mixedmethods, were conducted with staff from all levels of these organisations to investigate the relationship between adult learners’ professional development and organisations’ change agenda. Results indicated that in some situations there was considerable blurring of boundaries between informal and formal learning experiences. The conclusion is made that a balkanised approach to professional development is insufficient to build the capacity of learning professionals in the 21st Century and a more dynamic approach that moves flexibly between formal and informal learning approaches is recommended.